Cost data visualisation - Wood, Andrew; Kirkwood, Leigh; Feng, Zijin; Alhaydhal, Sultan; Alomran, Abdullah; Bin Taleb, Rayan; Durazo-Cardenas, Isidro; Starr, Andrew (IOS Press, 2021)
Decision making using the methodologies and analysis generated by the cost engineering function is widely considered good practice across industry, as a way to support both technical engineering decisions and fundamental business decisions. One persistent challenge for the professional cost engineer is to present cost data and information to decision makers and a mix of audiences. Data visualisation is therefore an important element to ensure that data is presented in a clear, effective and convenient format to ensure sufficient insights can be gathered. This work explores different data presentation and visualisation approaches. This review highlighted this topic as a research gap that this paper is novel in addressing. The review findings are further explored through a series of semi-structured interviews with experts in relevant fields to establish effective data visualisation methods, along with the challenges associated with presenting cost data to a variety of audiences. Chart embellishments are one explored area of potential to increase the engagement and understanding of visualisations.
Keywords: Cost-engineering; data visualisation; data